Assessing isometric kicking force and post-match responses using the Kicker test. Issue 11 (3rd June 2022) - Thomas, Rees J; Timmins, Ryan G; Tofari, Paul J; Williams, Morgan D; Opar, David A
ABSTRACT: This study examined the inter-session reliability of force output from a novel isometric strength assessment protocol (the Kicker); and its suitability to monitor soccer player's combined hip flexion and knee extension force capacity over 72-h post-competitive matches. Reliability (Part-A) testing was completed over three sessions on 20 individuals participating in various sports at a recreational level or higher. Post-match strength response (Part-B) data were collected for 72-h after a game (24-h (+24), 48-h (+48) and 72-h (+72) post-match) in 17 male academy soccer players. After familiarisation, Kicker force for each limb showed high inter-session reliability (ICC >0.95; typical error <14 N, CV <6%); minimum detectable change at a 95% confidence interval <40 N). Across the 72-h post-match period, Kicker force for each limb was suppressed compared to baseline (force loss range = −5.8% to −12.5%; effect sizes range = −0.26 to −0.43) at all time points. The Kicker assessment protocol measures combined isometric hip flexor and knee extensor force capacity with high inter-session reliability. The proof of concept that the protocol can be used as a monitoring tool was evidenced by sustained suppression of baseline force capacity in both kicking limbs for 72-h post soccer matches.